"I can be a mum or a professional, but not both": What women say about their experiences of juggling paid employment with motherhood. Issue 3 (11th September 2019) - Coombe, Jacqueline; Loxton, Deb; Tooth, Leigh; Byles, Julie
Abstract: Past research has identified the salience of the notion of "good motherhood" in countries such as Australia, where women are expected to invest significant time and energy, often through self‐sacrifice, to raise their children. We analysed free‐text comments provided in response to an open‐ended question from the Australian Longitudinal Study on Women's Health (ALSWH) to examine whether the discourse of "good motherhood" played any role in how women articulate their experiences of juggling paid employment with motherhood. Eighty women from the cohort born 1973–78 were included, providing 223 comments. "Good motherhood" underpinned many of the accounts about combining motherhood with paid employment. Women reported life as stressful and hectic as they attempted to juggle the demands of childcare with paid employment and domestic chores. Although some identified "good motherhood" as an unachievable ideal, most were largely unable to disengage with this discourse. Broader social structures, such as inflexible working conditions, were found to reinforce and support this ideal, contributing to the strength of the discourse.